Participation and Contraceptive Use among Women of Childbearing Age in Daerah Istimewa Yogyakarta Province: Further Analysis from IDHS 2017 - Tuffahati Nadhifa Srihadini; Amiza Husna; Lisa Mustafidatul Fauziah; Heldi Yusup; Wiwik Puji Mulyani; Seri Aryati; Umi Listyaningsih; Sri Rum Giyarsih; Slamet Suprayogi (Populasi, 2022)
Participation and selection of contraceptive methods may vary by region. It depends on the conditions of the region and the characteristics of the population in the region. Decision- making regarding participation and selection of contraceptive methods is influenced by various factors. Based on this description, this study aims to determine participation and selection of contraceptive use in Daerah Istimewa Yogyakarta Province based on educational level and number of living children owned by women of childbearing age. This research method uses further analysis of the 2017 Indonesian Health Demographic Survey (IDHS) data for the women of the childbearing age section. The analytical method used is a descriptive analysis by use of cross tabulation with IBM SPSS software. The results of the study indicate that higher education does not necessarily have a high percentage of contraceptive use, however, the variable number of children has an influence on the participation of contraceptives by women of childbearing age. We found that women with ≤ 2 children still want to have more children and tend to use less effective methods (short-term contraceptive method), while women with > 2 children use long-term contraceptive methods as a more effective method because they want to limit the number of children.